The new rulers of the world - Pilger, John (Verso, 2016)
aJohn Pilger's television film The New Rulers of the World was, among much else, a debunking of the myth of globalization. Reporting from Indonesia, he revealed how General Suharto's bloody seizure of power in the 1960s was part of a western design that was just the beginning of the imposition of a 'global economy' upon Asia. Now, he has collected both original work and expanded versions of his recent essays on power, its secrets and illusions in a book that illuminates the nature of modern imperialism. He discloses how up to a million Indonesians dies as the price for being the World Bank's 'model pupil', and the price paid by the people of Iraq for the West's decade-long embargo on that country. He returns to his homeland, Australia, to look behind the hype that led to the Millennium Olympics in Sydney and to reflect on Australia's continuing subjugation of its Aboriginal people. And, following the September 11 attacks on America and the bombing of Afghanistan, he describes the new thrust of American power and its goal of 'world order', as well as the propaganda that justifies and drives it.